Eradicating Bullying, Creating a Safe and Comfortable Learning Environment through Child-Friendly Schools - Diana Susanti; Sevia Diana Safitri; Faizin Faizin; M Aqil Fahmi Sanjani; Musammil Lateh (Early Childhood Development Gazette, 2025)
This research explores the optimal application of the Child-Friendly School (SRA)-based approach across various cultural contexts to eliminate bullying and create a safe, comfortable learning environment. The study was conducted at Aisyiyah Bustanul Athfal Jatinom Kindergarten in Blitar Regency, using a qualitative approach with a case study design. Data collection involved desk reviews, participatory observation, in-depth interviews with teachers, students, and parents, as well as focus group discussions (FGD). The data was analyzed through reduction, presentation, verification, content analysis, and interpretation. The findings reveal that the success of the SRA program hinges on three key factors: a well-structured program, such as class agreements and sessions focused on positive values; a supportive school environment, complete with counseling facilities and anti-bullying media; and active parental involvement in monitoring and reinforcing children’s values. This research suggests that implementing SRA not only helps reduce bullying incidents but also fosters an inclusive school culture and supports the development of positive student character. The study recommends extending the research to diverse regions and cultural settings to ensure the program's sustainability and to provide a foundation for more adaptive and inclusive education policies.